Ex Post Modernism: How the First Amendment Framed Nonrepresentational Art - Bonneau, Sonya G. (The Columbia Journal of Law & the Arts, 2016)
Postmodernism’s conceptual orientation and dissolution of boundaries might First Amendment law’s broadly inclusive marketplace of ideas, but instead art and law speak past one another. The result of Jackson Pollock as the exemplar of constitutionally covered visual art is not simply a matter of over- or underinclusion, but a doctrine and discourse that is reductive, anachronistic, and culturally alienated.2